Umeščanje novega mladinskega centra v skupnost - Vrhovec, Neža (Socialno delo, 2024)
A case study of a newly established youth center in a suburban neighborhood is presented. Opinions about this were collected from the director of this public institution, youth workers and young participants. The study was guided by two questions: how to establish a youth center as a community space in the neighbourhood, and how to encourage the participation of young people in it. The findings show that the cooperation of various stakeholders and residents is key to gaining local community support for the youth center, and that the development of activities should be based on participatory processes in the community. Youth workers encourage the participation of residents and young participants by establishing a dialogue, where they can express their ideas and needs, and then youth workers can adapt activities accordingly, include them as assistants and collaborators in activities and care for the space, or enable them to realize their own projects, and provide them with appropriate support and company of peers. Participation contributes to the strengthening of trust and connection between people in the community.
Keywords: mladi; mladinski delavci; mladinsko delo; outreach; participacija; participation; socialisation; socializacija; terensko delo; youth; youth workers